Formation of a Nanorod-Assembled TiO2 ActinomorphicFlower-like Microsphere Film via Ta Doping Using a Facile Solution Immersion Method for Humidity Sensing - Mohamed Zahidi, Musa; Mamat, Mohamad Hafiz; A Subki, A Shamsul Rahimi; Abdullah, Mohd Hanapiah; Hassan, Hamizura; Ahmad, Mohd Khairul; Abu Bakar, Suriani; Mohamed, Azmi; Bunsho Ohtani, Bunsho Ohtani (Mdpi, 2023)
This study fabricated tantalum (Ta)-doped titanium dioxide with a unique nanorodassembled actinomorphic-flower-like microsphere structured film. The Ta-doped TiO2 actinomorphicflower-like microsphere (TAFM) was fabricated via the solution immersion method in a Schott bottle with a home-made improvised clamp. The samples were characterised using FESEM, HRTEM, XRD, Raman, XPS, and Hall effect measurements for their structural and electrical properties. Compared to the undoped sample, the rutile-phased TAFM sample had finer nanorods with an average 42 nm diameter assembled to form microsphere-like structures. It also had higher oxygen vacancy sites, electron concentration, and mobility. In addition, a reversed double-beam photoacoustic spectroscopy measurement was performed for TAFM, revealing that the sample had a high electron trap density of up to 2.5 µmolg1. The TAFM showed promising results when employed as the resistive-type sensing film for a humidity sensor, with the highest sensor response of 53,909% obtained at 3 at.% Ta doping. Adding rGO to 3 at.% TAFM further improved the sensor response to 232,152%